2023
DOI: 10.1096/fj.202300067r
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of miR‐184 in zebrafish leads to ocular abnormalities by elevating p21 levels

Abstract: miR‐184 is one of the most abundant miRNAs expressed in the lens and corneal tissue. Mutations in the seed region of miR‐184 are responsible for inherited anterior segment dysgenesis. Animal models recapitulating miR‐184‐related anterior segment dysgenesis are still lacking, and the molecular basis of ocular abnormalities caused by miR‐184 dysfunction has not been well elucidated in vivo. In the present study, we constructed a miR‐184−/− zebrafish line by destroying both two dre‐mir‐184 paralogs with CRISPR‐Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(128 reference statements)
0
2
0
Order By: Relevance
“… 73 , 76 A recent study found that knocking out miR-184 in zebrafish did not affect embryonic lens development, but these miR-184–deficient zebrafish experienced microphthalmia and cataracts as adults, with no apparent corneal abnormalities. 77 The smaller lens size in these fish was attributed to reduced proliferation and fibrosis that was accompanied by elevated mRNA levels for cdkn1a and reduced transcripts for transcription factors hsf4 , ctcf , and sox9a . A previous report of miR-184 deletion in mice described homozygotes as having elevated levels of TP63 and epidermal hyperplasia.…”
Section: Discussionmentioning
confidence: 94%
“… 73 , 76 A recent study found that knocking out miR-184 in zebrafish did not affect embryonic lens development, but these miR-184–deficient zebrafish experienced microphthalmia and cataracts as adults, with no apparent corneal abnormalities. 77 The smaller lens size in these fish was attributed to reduced proliferation and fibrosis that was accompanied by elevated mRNA levels for cdkn1a and reduced transcripts for transcription factors hsf4 , ctcf , and sox9a . A previous report of miR-184 deletion in mice described homozygotes as having elevated levels of TP63 and epidermal hyperplasia.…”
Section: Discussionmentioning
confidence: 94%
“…Multiple previous reports have associated a point mutation (+57 C>T) in the seed region of miR-184 associated with human ocular abnormalities, including autosomal dominant severe keratoconus and early onset anterior polar cataract [65][66][67][68] , autosomal dominant endothelial dystrophy, iris hypoplasia, congenital cataract, and stromal thinning (EDICT) 65,68 . A recent study found that knocking out miR-184 in zebrafish did not affect embryonic lens development, but these miR-184-deficient zebrafish experienced microphthalmia and cataracts as adults, with no apparent corneal abnormalities 69 . The smaller lens size in these fish was attributed to reduced 29 proliferation and fibrosis that was accompanied by elevated mRNA levels for cdkn1a and reduced transcripts for transcription factors hsf4, ctcf, and sox9a.…”
Section: Discussionmentioning
confidence: 99%